A promising cosmopolitan biomonitor of potentially toxic elements in freshwater ecosystems: concentration gradients in sensitive areas. (February 2020) - Bellino, Alessandro; Alfani, Anna; De Riso, Laura; Gregorio, Romano; Pellegrino, Tommaso; Baldantoni, Daniela
Highlights: M. aquatica is a promising cosmopolitan biomonitor of PTEs in freshwater ecosystems. M. aquatica roots can accumulate PTEs over wide concentration ranges. The joint use of two selected hydrophytes enhanced biomonitoring accuracy. Spatial and temporal PTE concentration gradients were highlighted in a sensitive area. High Cd, Cr, Ni and Zn concentrations were observed near three karst springs. Abstract: Environmental monitoring in sensitive areas is crucial to develop and adapt governance policies. In this context, biomonitoring provides information not only on environmental contamination gradients, but also on the actual pollutant bioavailabilities and, using bioaccumulators, on their possible transfer through the food webs. The spatial distribution of suitable bioaccumulators, however, may limit the effectiveness of biomonitoring. To relieve this constraint, we investigated the usefulness of Mentha aquatica as a novel cosmopolitan biomonitor of potentially toxic elements (PTEs) in freshwater ecosystems, using Helosciadium nodiflorum, a widely recognized biomonitor, as a reference for environmental concentration gradients. The biomonitors were then employed in deriving spatial gradients of macronutrient (Ca, K, Mg, P, S), micronutrient (Co, Cr, Cu, Fe, Mn, Na, Ni, Si, V, Zn) and non-essential element (Al, As, Cd, Pb) concentrations in the area of one of the largest Italian national parks. Over two years and a large number of sites, M. aquatica roots provided PTE concentration gradients comparable to those obtained using H. nodiflorum roots, demonstrating their usefulness in PTE biomonitoring and widening the range of suitable biomonitors for freshwater ecosystems. At the same time, the joint use of M. aquatica and H. nodiflorum enhanced the accuracy of concentration gradients measured in two of the main freshwater ecosystems within the "Cilento, Vallo di Diano e Alburni" National Park (southern Italy). The study, performed for two consecutive years over 43 sites along the Bussento and Calore Salernitano rivers, pointed out several criticalities, attributable either to natural or anthropogenic sources. High natural concentrations of Al, As, Na, Si and V were mainly related to local characteristics (proximity to sea, sediment texture) or generalized lithological background (pyroclastic deposits on carbonates), whereas local high concentrations of Co, Fe and Mn were mainly related to direct or indirect anthropogenic sources (proximity to urban centers, wastewater treatment plants). Moreover, unusual high concentrations of Cd, Cr, Ni and Zn were observed at three spring mouths, suggesting changes in their bioavailability due to spring water physico-chemistry.